Ecological risk assessment of elemental pollution in sediment from Tunku Abdul Rahman National Park, Sabah - Md Suhaimi, Elias; Mohd Suhaimi, Hamzah; Shamsiah, Ab Rahman; Nazaratul Ashifa, Abdullah Salim; Wee, Boon Siong; Ezwiza, Sanuri (AIP Publishing, 2014)
Eleven (11) surface sediment samples were collected from Tunku Abdul Rahman National Park, Sabah. The neutron activation analysis (NAA) and inductively coupled plasma-mass spectrometry (ICP-MS) techniques were applied for the determinations metal contents and their distributions in sediment samples. The results shown that Arsenic (As) concentrations are enriched at all sampling stations except for station TAR 09, with enrichment factor (EF) values ranged from 1.1 to 7.2. The elements such as Cd, Cr, Sb and U showed enrichment at a few stations and other elements (Cr, Cu, Pb, Th, Zn) shown as background levels in all stations. Degrees of contamination in this study were calculated base on concentrations of six elements (As, Cd, Cr, Cu, Pb, and Zn). TAR 11 station can be categorized as very high degree of contamination with degree of contamination value of 43.2. TAR 07 station can be categorized as a considerable degree of contamination (contamination value of 16.9). Six stations (TAR 01, 03, 04, 05, 06, 08, 10) showed moderate degree of contamination, with contamination values ranging from 8.0 to 16.0. TAR 02 and TAR 09 stations showed low degree of contaminations (< 8.0). TAR 11 showed very high ecological risk index (RI) with RI value is 916. TAR 07 and TAR 10 showed moderate ecological risk index with RI value 263 and 213, respectively. Other stations showed low ecological risk with RI values ranging from 42.3 to 117 (< 150). Very high ecological risk index could give an adverse effect to the benthic organism. The data obtained from the enrichment factor, degree of contamination and ecological risk index provided vital information, which can be used for future comparison. Information from the present study will be useful to the relevant government agencies and authorities in preparing preventive action to control direct discharge of heavy metals from industries, agro-base activities and domestic waste to the rivers and the sea.